Catastrophic Out-of-Pocket Health Expenditure Among Rural Households in the Semi-Pastoral Community, Western Ethiopia: A Community-Based Cross-Sectional Study - Shikuro D; Yitayal M; Kebede A; Debie A (Dove Medical Press, 2020)
Debelo Shikuro,1 Mezgebu Yitayal,2 Adane Kebede,2 Ayal Debie2 1Benshangul-Gumuz National Regional State Health Bureau, Assossa, Ethiopia; 2Department of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Mezgebu YitayalDepartment of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, P. O. Box 196, Gondar, EthiopiaTel +251 947057683Email mezgebuy@gmail.comBackground: Every year, 808 million people face catastrophic health expenditure (CHE), and 122 million people were pushed into poverty. It aggravates healthcare inequalities, incurs double burden opportunity costs, and pushes households to sit in a deep poverty trap. A few studies have been done so far; however, it is not enough to inform policy decisions. Therefore, this study aimed to assess the catastrophic out-of-pocket health expenditure and associated factors among rural households in Mandura District, Western Ethiopia.Methods: We conducted a community-based cross-sectional study among the Mandura district’s 488 rural households from April to May 2017. We used a multistage systematic sampling technique to select the participants. We fitted a binary logistic regression model to identify the factors associated with catastrophic out-of-pocket health expenditure. We used the adjusted odds ratio (AOR) with 95% CI and the p-value < 0.05 to determine the variables associated with catastrophic out-of-pocket health expenditure.Results: Catastrophic health expenditure (CHE) with a 40% capacity to pay (CTP) households in the study area was 22.5%. Female household head (AOR = 2.92; 95% CI: 1.44, 5.93) and household with chronic illnesses (AOR = 3.93; 95% CI: 1.78, 9.14) were positively associated with CHE and, while households who had adult household members (AOR = 0.32; 95% CI: 0.16, 0.63) were negatively associated.Conclusion: The overall CHE, with a 40% CTP threshold, was high. Prevention of chronic illness might help to reduce the burden of the expenditure. Strengthening financial risk protection mechanisms, such as community-based health insurance, could help bring healthcare services equity.Keywords: catastrophic out-of-pocket health expenditure, semi-pastoral community, Ethiopia